2011
DOI: 10.1103/physrevlett.106.156805
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electron-Electron Interaction in Quantum Hall Systems with Scanning Tunneling Spectroscopy

Abstract: Using low-temperature scanning tunneling spectroscopy applied to the Cs-induced two-dimensional electron system (2DES) on p-type InSb(110), we probe electron-electron interaction effects in the quantum Hall regime. The 2DES is decoupled from bulk states and exhibits spreading resistance within the insulating quantum Hall phases. In quantitative agreement with calculations we find an exchange enhancement of the spin splitting. Moreover, we observe that both the spatially averaged as well as the local density of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…We note that our theoretical results are consistent with available data on scanning tunneling microscopy in disordered interacting systems, in particular, for a strongly disordered 3D system [68], for various 2D semiconductor systems and graphene [69][70][71][72], for a magnetic semiconductor Ga 1−x Mn x As near metal-insulator transition [9], for metallic and insulating phases near superconductorinsulator transition in TiN, InO, and NbN films [73][74][75][76][77][78].…”
Section: Pacssupporting
confidence: 87%
“…We note that our theoretical results are consistent with available data on scanning tunneling microscopy in disordered interacting systems, in particular, for a strongly disordered 3D system [68], for various 2D semiconductor systems and graphene [69][70][71][72], for a magnetic semiconductor Ga 1−x Mn x As near metal-insulator transition [9], for metallic and insulating phases near superconductorinsulator transition in TiN, InO, and NbN films [73][74][75][76][77][78].…”
Section: Pacssupporting
confidence: 87%
“…Tunneling spectroscopy in van der Waals and other heterostructures is a powerful tool that can reveal unique information about the density of states (DOS) of the electrodes [1,2], about phonons (or other excitations) [3][4][5], about the chiral, valley [6] and spin states of the carriers [7,8] and their interactions [9]. Recently it was shown that the presence of defects in crystalline hexagonal boron nitride (h-BN) tunneling barriers can be detected in the tunneling spectra, which is dominated by Coulomb blockade effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…While the existence of the edge states was confirmed indirectly by transport measurements [4,5], the condition for observation of the edge states and the details of the potential and density profiles are still unclear experimentally. Continuous effort has been made, therefore, to directly probe alternating strips of the edge states, for example, by scanning single electron transistors [6], subsurface charge accumulation [7], scanning force microscope [8][9][10], and scanning tunneling spectroscopy [11,12]. Scanning gate microscopy [13,14] has been used to image electron flow from a quantum point contact in magnetic fields.…”
mentioning
confidence: 99%